Functional and environmental impacts of the use of reclaimed asphalt pavement materials and of foamed asphalt - Saleh, Ali; Gáspár, László (Acta Technica Jaurinensis, 2021)
Environmental safety related to asphalt mixing plants has been a growing concern due to the high temperature of asphalt mixture production resulting in a lot of energy used and much air pollutants released. Asphalt mixtures with foamed bitumen and RAP can reduce this problem. This paper deals with their functional and environmental effects. In the paper, it was introduced that the hot mix asphalt mixtures bound by foamed bitumen and containing RAP materials provides a good workability, in comparison to “traditional” hot mix asphalt mixtures. However, producing foamed bitumen needs special technological steps before using it as asphalt binder. The use of RAP materials reduces environmental harm and construction costs, besides it preserves the limited resources of stone, sand and gravel.